Effect of systemic BCG infection in syrian golden hamsters. - Zwilling, B S (1976)
The response of Syrian golden hamsters to systemic infection with several doses of Mycobacterium bovis (strain BCG) was assessed. Large numbers of organisms (10(7)), injected intravenously, were lethal for hamsters, whereas all animals survived infection with 10(4) colony-forming units of BCG. Animals responded immunologically to purified protein derivative as assessed by increased footpad swelling and splenic lymphocyte proliferation. The immediate cause of death was a diffuse granulomatous interstitial pneumonia.